IL-34 Expression Is Reduced in Hashimoto's Thyroiditis and Associated With Thyrocyte Apoptosis - Wang, Shuo; Liu, Yongping; Zhao, Na; Cui, Xuejiao; Huang, Mingshi; Li, Yushu; Shan, Zhongyan; Teng, Weiping (Frontiers in Endocrinology, 2018)
Hashimoto's thyroiditis (HT) is a common autoimmune disease accompanied by lymphocyte infiltration and thyroid tissue destruction. IL-34 was first described in 2008, and its involvement in the development of many autoimmune diseases has been recently identified. However, whether IL-34 is a regulatory factor in HT is unclear. Here, we demonstrate that IL-34 is expressed on thyroid follicular epithelial cells and that IL-34 expression is significantly reduced in thyroid tissue in patients with HT and spontaneous autoimmune thyroiditis (SAT) models. Serum IL-34 levels in patients with HT are also significantly reduced. In addition, IL-34 is associated with thyroid autoantibodies in both thyroid tissue and serum. Furthermore, our data show that IL-34 participates in the apoptosis resistance of thyrocytes in HT induced by CSF-1R and may be a potential indicator for evaluating thyrocyte damage.